The Effectiveness of Three Biofilter Media on Total Ammonia Nitrogen (TAN) Removal and Survival Rate of Tilapia Gift Seeds (Oreochromis niloticus) in Recirculation Aquaculture System - Mira Andhika Pierrenia; Sri Rejeki; Dicky Harwanto (Journal Omni-Akuatika, 2021)
Efforts to increase tilapia production are carried out through intensive culture by taking into account various aspects that support fish survival. The culture system that supports intensive culture is the Recirculation Aquaculture System (RAS). The RAS technology has the ability to support aquaculture with very high density and high yields compared to open culture systems. This study aims to determine the effect of different biofilter media in RAS on decreasing TAN concentration and growth of tilapia seeds. The method used was experimental with three treatments and four replications. Tilapia with an average individual weight of 3.40 ± 0.15 g were maintained in RAS with three different biofilter media treatments, sand (A), polystyrene microbeads (B) and kaldnes (C). The parameters observed were pH, DO, temperature, TAN removal efficiency, specific growth rate (SGR) and survival rate (SR). The results showed that different biofilter media had a significant effect (P <0.05) on the TAN removal efficiency value but had no significant effect (P> 0.05) on the SGR and SR values. The sand biofilter treatment (A) gave the best TAN removal efficiency of 36.61±4.82%.Key words: Kaldnes, Polystyrene, Sand, TAN, Tilapia